Structure and crystallography of foliated and chalk shell microstructures of the oyster Magallana: the same materials grown under different conditions - Antonio G. Checa (Nature Portfolio, 2018)
Abstract Oyster shells are mainly composed of layers of foliated microstructure and lenses of chalk, a highly porous, apparently poorly organized and mechanically weak material. We performed a structural and crystallographic study of both materials, paying attention to the transitions between them. The morphology and crystallography of the laths comprising both microstructures are similar. The main differences were, in general, crystallographic orientation and texture. Whereas the foliated microstructure has a moderate sheet texture, with a defined 001 maximum, the chalk has a much weaker sheet texture, with a defined 011 maximum. This is striking because of the much more disorganized aspect of the chalk. We hypothesize that part of the unanticipated order is inherited from the foliated microstructure by means of, possibly, $${\boldsymbol{\{}}{\bf{01}}\bar{{\bf{1}}}{\bf{8}}{\boldsymbol{\}}}$$ {011¯8} twinning. Growth line distribution suggests that during chalk formation, the mantle separates from the previous shell several times faster than for the foliated material. A shortage of structural material causes the chalk to become highly porous and allows crystals to reorient at a high angle to the mantle surface, with which they continue to keep contact. In conclusion, both materials are structurally similar and the differences in orientation and aspect simply result from differences in growth conditions.